The pore-class dependent concentration of DOC in degraded fen peat soils - Cambinda, Rosa Tiimuma; Liu, Haojie; Lennartz, Bernd (Frontiers in Environmental Science, 2025)
Peatland carbon loss occurs via gaseous emissions and substantial aquatic fluxes of dissolved organic carbon (DOC) during peat mineralisation and degradation. While DOC mobilisation is known to be influenced by hydrological and microbial processes, the role of pore-scale structure, particularly pore-size class, remains underexplored. We hypothesised that DOC concentration is influenced by pore size, with finer pores yielding higher concentrations. Using topsoil and subsoil samples from a degraded fen peatland (average soil organic matter content: 34 wt% and 57 wt%, respectively), we extracted pore water at - 60 hPa (macropores) and - 600 hPa (mesopores). The degraded topsoil exhibited significantly higher DOC concentrations than the subsoil, with levels 1.7 times greater at - 60 hPa and 2.2 times higher at - 600 hPa. No significant difference in DOC concentrations was observed between macropores and mesopores in the subsoil domain; however, higher DOC concentrations were evident in mesopores (107.63 mg L-1) relative to macropores (85.46 mg L-1) in the topsoil domain. Our results demonstrate that DOC concentration from degraded fen peat soils are closely linked to pore structure, particularly pore-size class, bulk density, and total porosity. Elevated DOC concentrations and variability in degraded topsoil are also associated with heterogeneity in the quality of soil organic matter, with mesopores serving as key hotspots for DOC concentration due to their role in organic matter transformation and microbial activity. These findings highlight the necessity of integrating pore-scale physical properties into peatland restoration strategies to effectively mitigate persistent waterborne DOC export.